2009
DOI: 10.1111/j.1745-6592.2009.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Pore Water Characteristics Following a Release of Neat Ethanol onto Pre‐existing NAPL

Abstract: Neat ethanol (75.7 L) was released into the upper capillary zone in a continuous‐flow, sand‐packed aquifer tank (8.2 m3) with an average seepage velocity of 0.75 m/day. This model aquifer system contained a residual nonaqueous phase liquid (NAPL) that extended from the capillary zone to 10 cm below the water table. Maximum aqueous concentrations of ethanol were 20% v/v in the capillary zone and 0.08% in the saturated zone at 25 and 30 cm downgradient from the emplaced NAPL source, respectively. A bench‐scale r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…However, such a high concentration (>1% v:v) would likely occur for only high ethanol content fuels and would be confined to the capillary fringe near the source zone where a non-aqueous phase liquid (NAPL) phase exists Barker, 2011, 2013b;Stafford et al, 2009;Stafford and Rixey, 2011). Concentrations of dissolved ethanol in groundwater impacted by ethanol-blended fuels are usually lower than 10,000 mg/L (Corseuil et al, 2011;da Silva and Corseuil, 2012;Freitas and Barker, 2013a;Spalding et al, 2011).…”
Section: 2mentioning
confidence: 96%
“…However, such a high concentration (>1% v:v) would likely occur for only high ethanol content fuels and would be confined to the capillary fringe near the source zone where a non-aqueous phase liquid (NAPL) phase exists Barker, 2011, 2013b;Stafford et al, 2009;Stafford and Rixey, 2011). Concentrations of dissolved ethanol in groundwater impacted by ethanol-blended fuels are usually lower than 10,000 mg/L (Corseuil et al, 2011;da Silva and Corseuil, 2012;Freitas and Barker, 2013a;Spalding et al, 2011).…”
Section: 2mentioning
confidence: 96%
“…Oxygen intrusion into anaerobic contaminated plumes (e.g., due to natural recharge from surrounding groundwater and from the surface) is a common phenomenon, and BTEX catabolism initiated by oxygenases has previously been observed at very low levels of dissolved oxygen (0.1 mg/L) (Costura and Alvarez 2000). Ethanol is highly soluble in water and tends to quickly partition into groundwater and migrate away from the source zone (Heermann and Powers 1998;Cápiro et al 2007), even though a small fraction can be retained in the pore water resulting in some mass transfer from the capillary zone into the groundwater (Stafford et al 2009). similar mechanisms as those reported for the common fuel additive, ethanol.…”
Section: Effects Of Soy Biodiesel On Hypoxic Biodegradation Of Toluenmentioning
confidence: 99%
“…This has been shown in laboratory tests using 2D boxes (Silliman et al 2002;Henry and Smith 2003;Berkowitz et al 2004). For example, Stafford et al (2009) found ethanol concentrations in the capillary fringe two orders of magnitude higher than just below the water table. For example, Stafford et al (2009) found ethanol concentrations in the capillary fringe two orders of magnitude higher than just below the water table.…”
Section: Introductionmentioning
confidence: 61%